Recessive mutations in MSTO1 cause mitochondrial dynamics impairment, leading to myopathy and ataxia. Issue 8 (6th June 2017) - Nasca, Alessia; Scotton, Chiara; Zaharieva, Irina; Neri, Marcella; Selvatici, Rita; Magnusson, Olafur Thor; Gal, Aniko; Weaver, David; Rossi, Rachele; Armaroli, Annarita; Pane, Marika; Phadke, Rahul; et al.
Abstract : – We identified by WES biallelic mutations in MSTO1 in two families – MSTO1‐mutant patients presented a multisystem complex phenotype characterized by myopathy and cerebellar ataxia. – MSTO1 is a cytosolic protein modulating mitochondrial dynamics Abstract: We report here the first families carrying recessive variants in the MSTO1 gene: compound heterozygous mutations were identified in two sisters and in an unrelated singleton case, who presented a multisystem complex phenotype mainly characterized by myopathy and cerebellar ataxia. Human MSTO1 is a poorly studied protein, suggested to have mitochondrial localization and to regulate morphology and distribution of mitochondria. As for other mutations affecting genes involved in mitochondrial dynamics, no biochemical defects typical of mitochondrial disorders were reported. Studies in patients' fibroblasts revealed that MSTO1 protein levels were strongly reduced, the mitochondrial network was fragmented, and the fusion events among mitochondria were decreased, confirming the deleterious effect of the identified variants and the role of MSTO1 in modulating mitochondrial dynamics. We also found that MSTO1 is mainly a cytosolic protein. These findings indicate recessive mutations in MSTO1 as a new cause for inherited neuromuscular disorders with multisystem features.